2017
DOI: 10.3168/jds.2016-11880
|View full text |Cite
|
Sign up to set email alerts
|

The influence of postnatal nutrition on reproductive tract and endometrial gland development in dairy calves

Abstract: Uterine gland development occurs after birth in cattle and other mammals. The timeline of gland development has been described in various species, but little is known about how postnatal diet influences uterine gland development. This is especially concerning in dairy heifers, where a variety of milk replacer and whole milk nutrition options exist. Little work also exists in cattle to describe how early exposure to steroids influences reproductive tract and uterine gland development. The objective of this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In the present study, although endometrial thickness was greater from 26 to 33 wk of age in heifers that received the high postweaning diet than in those that received the low postweaning diet, it did not differ between the preweaning diet groups. Using a different approach to compare dietary planes of nutrition, Wilson et al (2017) compared calves that were fed restricted versus enhanced milk replacer diets and observed reduced number and size of uterine glands at 8 wk of age in calves receiving the restricted milk replacer diet. Interestingly, however, they reported that the negative effect of restricted versus enhanced milk replacer diet observed on uterine glandular development at 8 wk of age was no longer evident 2 wk after weaning (Wilson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, although endometrial thickness was greater from 26 to 33 wk of age in heifers that received the high postweaning diet than in those that received the low postweaning diet, it did not differ between the preweaning diet groups. Using a different approach to compare dietary planes of nutrition, Wilson et al (2017) compared calves that were fed restricted versus enhanced milk replacer diets and observed reduced number and size of uterine glands at 8 wk of age in calves receiving the restricted milk replacer diet. Interestingly, however, they reported that the negative effect of restricted versus enhanced milk replacer diet observed on uterine glandular development at 8 wk of age was no longer evident 2 wk after weaning (Wilson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Using a different approach to compare dietary planes of nutrition, Wilson et al (2017) compared calves that were fed restricted versus enhanced milk replacer diets and observed reduced number and size of uterine glands at 8 wk of age in calves receiving the restricted milk replacer diet. Interestingly, however, they reported that the negative effect of restricted versus enhanced milk replacer diet observed on uterine glandular development at 8 wk of age was no longer evident 2 wk after weaning (Wilson et al, 2017). Notably, in the present study, the increase in endometrial thickness from 26 to 33 wk was not consistent among weeks in the high postweaning diet group (Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules are present in whole milk, and calves fed whole milk ad libitum were found to produce more milk during their first lactation than calves fed milk replacer ad libitum (Moallem et al, 2010). In addition to increased milk yield, enhanced organ growth, mammary gland development, and gut-associated immune system development were associated with a higher plane of preweaning nutrition (Geiger et al, 2016;Wilson et al, 2017;Hammon et al, 2018). Presumably, epigenetic mechanisms play a role in maintaining long-term effects of preweaning nutrition, accounting for stable alterations in the phenotype as a form of metabolic imprinting (Bartol et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased appreciation of the milk microbiome in establishment of the gut microbiome and modulation of immune responses (Rautava, 2016) further emphasizes the relevance of mammary secretions to neonatal development. A recent report (Wilson et al, 2017) showed that preweaned restricted-fed calves have impaired endometrial gland development and alterations in growth factor-related signaling molecules. This suggests that the level of nutrition or components in milk replacer can affect reproductive tract development in calves.…”
Section: Introductionmentioning
confidence: 99%